Career Choice As An Auditor: Analysis on Determinant Factors of Perguruan Tinggi Muhammadiyah and Aisyiyah (PTMA) in Central Java and D.I.Yogyakarta - Lintang, Kurniawati; Rita Wijayanti; Nur Kholis (Universitas Muhammadiyah Surakarta, 2024)
The aim of this research is to find out the factors influencing student dynamics in their choice of career as auditors. This is quantitative research with a student focus of the Accounting Studies Program on PTMA in Central Java and D.I. Yogyakarta to give a deeper understanding and consider the complex and diverse factors influencing individual career decisions, in particular the choice of career as an auditor. A sample of 243 respondents matched the purposive sampling criteria. Data analysis using SEM-PLS with SMARTPLSanalytical tool 3. The results of the research showed that 1) motivation is able to influence gender stereotypes in the choice of career as an auditor. 2) Financial appreciation is capable of influencing gender- stereotypes in the selection of a career as an auditor. 3) Market considerations are capable of affecting gender stereotypes when choosing a career in the role of auditor. More specifically, the results of this study show that motivation, financial appreciation, and market considerations do not directly affect career choices as an auditor.